Alcohol habits in Sweden during 1997–2018: a repeated cross-sectional study. (17th November 2019) - Källmén, Håkan; Berman, Anne H.; Elgán, Tobias H.; Wennberg, Peter
Abstract: Aims: This study describes changes in alcohol habits in age and gender strata among the Swedish general population during the 21-year period following the Swedish EU membership in 1995. Methods: The Alcohol Use Disorders Identification Test (AUDIT) was distributed as a postal questionnaire to randomly selected cross-sectional samples every fourth year, starting in 1997. Results: Six samples were included in this study. A comparison between 2014 and 2018 showed a tendency to decreasing average total AUDIT scores, particularly among men and in the youngest age group (Cohen's d = 0.28). Conclusion: The results should be understood in the context of declining response rates in this type of survey.